The Persian Way? Dingzhou Eye Ointment and Its Origins - Ge SONG; Yuting HE; Zhiheng GUO (Chinese Medicine and Culture)
Abstract. Dingzhou eye ointment gained significant popularity from the late Qing dynasty to the Republican era. Its legacy persists through three prominent families: Bai Jingyu (白敬宇), Ma Yinglong (马应龙) and Zhang Qizhu (张齐珠). Each family’s Dingzhou eye ointment is similar, with comparable ingredients, dosages, and usage methods, suggesting a common origin. While many well-established Dingzhou eye ointment brands claim their origins date back to the late Ming dynasty, the origins of its formulation are likely much older. In ancient Chinese medical texts, there were proto-formulations of similar eye ointments recorded during the Jin and Yuan dynasties, with comparable external and standardized eye medicine formulations appearing in the Ming and Qing dynasties. By the late Qing dynasty, Dingzhou eye ointment had become a popular mainstream topical eye treatment in traditional Chinese medicine. From a broader geographically perspective, the composition aligns with that of similar treatments used in Greco-Roman medicine, which combined minerals such as calamine with aromatic ingredients to create eye medicines. The principles behind the composition of Dingzhou eye ointment are in accord with the concept of the four humours in Arabian medicine. It is possible that the Hui ethnic group was responsible for the introduction of Dingzhou eye ointment to China, indicating cultural exchange between Chinese and foreign medicine practices.